In vitro bioactivities of anodised titanium in mixtrue of B-Glycerophosphate and calcium acetate for biomedical application - Lee, Te Chuan (2016)
Anodic oxidation has been widely used to modify the surface properties of titanium in order to improve the biocompatibility after implantation. In this study, high purity titanium foils were exposed in a mixture of β-glycerophosphate disodium salt pentahydrate (β-GP) and calcium acetate monohydrate (CA). The parameters for anodic oxidation method such as applied voltage (50-350 V), current density(10-70 mA.cm-2), electrolyte concentration (0.02 M β-GP + 0.2 M CA, 0.04 M β-GP + 0.04 M CA) , anodising time (5-10 mins), agitation speed (300-1500 rpm), ultrasonic amplitude (20-60 μm) and bath temperature (4-100 °C) were varied to investigate the impact on the surface properties of titanium. The results showed that surface of the titanium foil appeared to be highly porous and demonstrated high crystallinity as well as high hydrophilic properties especially when the parameters of anodic oxidation have been varied. This study also proposes two novel methods particularly to accelerate the bone-like apatite formation on the anodised titanium in a shorted time: (1) UV irradiation during in vitro testing and (2) adding additives in electrolyte. After soaked and irradiated with UV in simulated body fluid (SBF) for 7 days, highly crystallised bone-like apatite was fully covered on the anodised surface. Interestingly, the smooth and partially porous surface of the anodised titanium was observed to be fully covered by the bone-like apatite layer, which contradict previous research results. The mechanism for growth of bone-like apatite was developed and involved several stages from the existence of hydroxyl groups (•OH) under the UV irradiation has been disclosed thoroughly. Further, additives such as sulphuric acid (H2SO4), hydrogen peroxide (H2O2) and sodium hydroxide (NaOH) were added into the electrolyte were also able to accelerate the formation of bone-like apatite because of the presence of (•OH), tricalcium phosphate (Ca3O8P2), calcium diphosphate (Ca2O7P2), calcium titanate (CaTiO3) or sodium titanate (Na2Ti3O7) on the anodised surface, which able to induce the nucleation site of bone-like apatite.